(x-4)^2=(x-4)(x-4)
multiply the two xs,multiply
the two 4s multiply the first x
by the second 4 and multiply
the second x by the first 4
this gives:
x^2+16-4x-4x
=x^2+16 -8x
your answer was x^2+16,so
you forgot the -8x
in general,
(x-a)^2=x^2-2ax+a^2
remember the -2ax
i hope that this helps
2006-12-12 06:28:35
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
You can multiply expressions in the same manner as you multiply numbers.
43¨2 = 43*43
How do we do that in practice? We do (40+3)*43
which is 40*43 + 3*43 = 1720 + 129 = 1849
And we write it:
43
43
___
..129 (the periods are for spacing only)
172 (this number appears offset because we do not write the 0)
____
1849
Same with expressions:
(x-4)^2 = (x-4)*(x-4) = x*(x-4) - 4*(x-4) = x^2 -4x -4x +16
= x^2 -8 x +16.
We can write it the same way as we did for numbers:
x -4
x -4
-----
......-4x +16
x^2 -4x
--------------
x^2 -8x +16
2006-12-12 05:41:05
·
answer #2
·
answered by Raymond 7
·
0⤊
0⤋
OK expand the expression as shown below...
(x - 4) (x - 4)
Once this is done factor/foil each expression so you end up with this...
x2 - 4x - 4x =16
After you've done the factoring combine like terms and your final answer will look like this...
x2 -8x +16
X(squared) - 8x +16
2006-12-12 05:36:39
·
answer #3
·
answered by The Plague 4
·
0⤊
0⤋
(x - 4)^2 is
(x - 4)(x - 4)
Using FOIL (First, Outside Inside and Last)
it becomes
x^2 - 4x - 4x + 16
Collecting like terms
x^2 - 8x +16
2006-12-12 08:10:45
·
answer #4
·
answered by lenpol7 7
·
0⤊
0⤋
(x-4)² = (x-4)(x-4)
Using the rule for multiplying expressions contained in brackets FOIL (First, Outers, Inners, Last)...
(x-4)(x-4) = x²-4x-4x+16 = x²-8x+16
2006-12-12 05:40:53
·
answer #5
·
answered by forge close folks 3
·
0⤊
0⤋
x2 - 8x +16.
It's just a quadratic. multiply everything in each set of brackets by each element of the otuer bracket.
x(x-4) = x2 - 4x
-4(x-4) = -4x = 16
so, answer is x2 -4x - 4x +16 = x2 - 8x +16
2006-12-12 05:33:25
·
answer #6
·
answered by lulu 6
·
0⤊
0⤋
(x-4)(x-4)
= x squared - 8x +16
I think. It's been a long time. You have to remember to multiply everthing together (i.e. the two x's, the two 4's, AND the two x's with the two 4's)
2006-12-12 05:30:17
·
answer #7
·
answered by Mango M 2
·
0⤊
0⤋
(x-4)^2 = (x-4)(x-4) = x^2 - 4x -4x +16 = x^2 -8x +16
2006-12-12 05:29:33
·
answer #8
·
answered by Daniel P 2
·
0⤊
0⤋
(x-4)² = (x-4)(x-4) = x² - 4x - 4x + 16 = x² - 8x + 16
2006-12-12 10:19:46
·
answer #9
·
answered by Kemmy 6
·
0⤊
0⤋
I think that the answer is x2 - 42 ( all the twos are suppose to be squared.) becuase if the exponent in outside the brackets you multiply the exponents. and if there is no exponent shown you can assume it is a one.
2006-12-12 05:38:28
·
answer #10
·
answered by Anonymous
·
0⤊
1⤋